أسلوب التشويق في الدعوة إلى الله من خلال سورة الإنسان نموذجا - الخراط، زلفى أحمد محمد (جامعة القصيم, 2022)
يحرص الداعية على توخي الأساليب التي تُعينه على أداء رسالته في تحقيق خطاب دعوي جاذب ومؤثّر، يأمل منه الوصول إلى الثمرة المرجوة من الدعوة الإسلامية، وهي استجابة المدعو، وتطبيقه لما يدعى إليه. وأسلوب التشويق هو أحد الأساليب البلاغية التي يجدر بالداعية الإفادة منها، وتسخيرها في المجال الدعوي. فبالتشويق يجذب الداعية المدعو، ويثير مشاعره، ويحثه على التفكير فيما دعاه إليه، ويدفعه إلى الاستجابة، والالتزام بالرسالة التي عرضها عليه. وإن التشويق إلى الجنة هو أحد الأساليب الدعوية القرآنية، وقد استُخدم في الكثير من المواضع في ثنايا القرآن الكريم، وسور القرآن الكريم تحفل بالعديد من النماذج التشويقية. وفي هذا البحث تناولتُ بالدراسة مفهوم الأسلوب التشويقي وأهميته البلاغية، وأهمية أسلوب التشويق في الدعوة، بالإضافة إلى أهم الأساليب التشويقية في سورة الإنسان، والأغراض الدعوية لأسلوب التشويق في ضوء سورة الإنسان. The Da’ia (preacher) is keen to explore the best methods that would help him to perform his mission in composing an attractive and effective speech. By this method he hopes to reach the desired outcome of Islamic da'wa, which is attracting the invitee to accept the invitation. The technique of suspense is one of the rhetorical styles that a Da’ia would benefit from using when speaking in the missionary milieu. Through suspense, the Da’ia captures the attention of the invitee and stimulates his senses, urging him to think of what he is invited to accept and encouraging him to respond to the message with which he is presented . Excitement when thinking about Paradise is one of the Quranic da'wa methods used in many verses throughout the Holy Qur'an. The Qu’ran is replete with many examples of stimulating methods. In this study, the researcher addresses the concept of the method of suspense and its rhetorical importance in da'wa. In addition, the researcher addresses the most important styles of suspense used in the Surah “The Human” in the light of the chapter entitled “The Human."
Keywords: القرآن الكريم -- البلاغة القرآنية -- أسلوب التشويق -- سورة الإنسان